Bolton Tooth Size Discrepancy among Mosul Families - Wafaa Gh Al-Shahery (University of Mosul, College of Dentistry, 2013)
Aims: To determine the possible effect of genetic factor on Bolton tooth size discrepancy between siblings in families living in Mosul City (Iraq). Material and methods: The study sample included 126 subjects distributed between 45 families in Mosul City (Iraq), (56 females and 70 males) whose ages ranged between (20- 35) years. The sibling pairs were divided into three groups according to gender: male -male (24 pairs), female-female (18pairs), male-female (21 pairs). Electronic digital vernire with fine tips was used to measure the maximum mesio-distal widths of the teeth, and Bolton anterior and over all ratios was calculated. The effect of Heritability on Bolton ratios was studied by means of Har-vey's mixed model least-squares and maximum likelihood computer program (LSMLMW) model type II. Results: Statistical analysis showed that Heritability was effective on Bolton tooth-size discrepancy in all groups, with the higher means for the anterior and over all ratios are for the male- male group. While the female-male group showed the lowest mean for the anterior ratio and the female -female group showed the lowest mean for the overall ratio. Conclusions: Siblings showed similar malocclusions, and examination of older sibling can provide clues to the need for interception and early treatment of malocclusion.